Implementasi Kurikulum 2013 Di SMA Kota Serang Menuju Sekolah Unggulan - Ida Farida; Anisa Tulhalizah; Aisyah Sekar Tri Wardani; Putri Kiki Lestari (Concept: Journal of Social Humanities and Education, 2023)
An adequate and modern curriculum system is needed to support quality education. So that the learning process can form and develop students to be skilled and have good character education. This research was conducted because it has the aim of knowing comprehensively about the implementation of the 2013 curriculum at SMAN 1 Kota Serang. In implementing the 2013 curriculum, it is hoped that students will be more enthusiastic about learning so that the process carried out can run optimally. SMAN 1 Serang City Can become a superior school that can produce outstanding students who are ready to be competitive in the national or international arena. By applying the 2013 curriculum appropriately, it can build a conducive learning environment and can add to students' understanding when studying in class. The process of implementing a good and clear curriculum requires formulating goals, organizing learning experiences, organizing materials, needs, and developing evaluation tools. Thus, it will be easier to implement the curriculum at SMAN 1 Serang City to become a quality superior school to help students who will later enter college get good grades. Because if seen from the truth, the 2013 curriculum has a very significant role because it can help students learn to ask questions during learning related to the learning conveyed by the teacher, have objective reasoning power, make observations, and be able to present the results of their learning to the teacher by good for good results.